Mutation of rpoB Shifts the Nutrient Threshold Triggering Myxococcus Multicellular Development - Eisner, Sabrina A.; Velicer, Gregory J.; Yu, Yuen-Tsu N. (Frontiers in Microbiology, 2022)
The ability to perceive and respond to environmental change is essential to all organisms. In response to nutrient depletion, cells of the soil-dwelling δ-proteobacterium Myxococcus xanthus undergo collective morphogenesis into multicellular fruiting bodies and transform into stress-resistant spores. This process is strictly regulated by gene networks that incorporate both inter- and intracellular signals. While commonly studied M. xanthus reference strains and some natural isolates undergo development only in nutrient-poor conditions, some lab mutants and other natural isolates commit to development at much higher nutrient levels, but mechanisms enabling such rich medium development remain elusive. Here we investigate the genetic basis of rich medium development in one mutant and find that a single amino acid change (S534L) in RpoB, the β-subunit of RNA polymerase, is responsible for the phenotype. Ectopic expression of the mutant rpoB allele was sufficient to induce nutrient-rich development. These results suggest that the universal bacterial transcription machinery bearing the altered β-subunit can relax regulation of developmental genes that are normally strictly controlled by the bacterial stringent response. Moreover, the mutation also pleiotropically mediates a tradeoff in fitness during vegetative growth between high vs. low nutrient conditions and generates resistance to exploitation by a developmental cheater. Our findings reveal a previously unknown connection between the universal transcription machinery and one of the most behaviorally complex responses to environmental stress found among bacteria.